Implementasi Pencatatan Perkawinan Pada Kua Kota Makassar (Telaah Undang-Undang No 1 Tahun 1974) - Muhammadong Muhammadong (Al-Hikmah Journal for Religious Studies, 2014)
This research is designed to provide a model as system of marriage recording at KUA Makassar in order to achieve regularity in giving service to society and not raise danger to the spouse who want to celebrate their marriage. Therefore, the marriage recording at KUA of Makassar becomes easy to be applied. So, no one is harmed when there is spouse celebrating the marriage. In Islam, marriage recording refers to give assurance and protection to the spouse. It is included of cause and effect in marriage. It is such as right and obligation interrelationship, the children were born, and the right of the children to get inheritance. It becomes legal if it is based on condition and pillar of marriage in Islam which is recorded at KUA. It can avoid illegal marriage and unrecorded in KUA or registar book because they are unknown and unwareness of the important of marriage document. It  is  included  of  avoding  to  pass  somebody  by  doing  Poligami, keeping subsidy to the wives who are divorced. One of the dilemma to unrecord at KUA Makassar, it is because soceities have unawareness law. In other hand, soceities is apathetic in rules of marriage, because there is regulation of marriage recording unclear and Poligamy is still complicated. Therefore, many people set the law at defiance about Marriage.